Η χρονική εξέλιξη του επιπολασμού του άσθματος και αλλεργιών στα παιδιά σε αστικές και σε αγροτικές περιοχές της Κύπρου - Αναστασιάδου, Ερμιόνη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: The prevalence of childhood asthma and allergies in Cyprus seems to have had a greater increase in the last decade in the rural areas of Cyprus. Indeed, in contrast to 2001 when asthma and allergies was higher in urban areas, in 2008 the prevalence of asthma and allergies do Όχιt seem to be at different levels in both urban and rural areas. Purpose: This study aims to explore alternative ways of classifying areas into rural or urbanto assess temporal changes in the prevalence of asthma and allergies in Cypriot children in a period of 8 years from 2001 to 2008. Material and Methods: During the academic years 1999-2000 and 2007-2008, parents of children 7-8 years (N = 4944 and N = 2216, respectively), residing in the same proportion of the total urban and rural areas of Cyprus completed the questionnaire type ISAAC. Results: The prevalence of current wheeze was higher in 2008 (8.9%, 95% confidence interval: 7.6% -10.3%, n = 2216) compare to 2000 (6.5%, 95% CI: 5.7% -7.5%, n = 4944). Significant increases were also observed in the diagΌχιsis of asthma (11% vs. 17.9%), the symptoms of eczema (3.7% vs. 4.7%) and diagΌχιsis of eczema (11% vs. 17.9%). The prevalence of current wheeze almost doubled between 2000 and 2008 in rural areas (5.7% vs. 8.4%, or 1.50, CI: 0.90 – 2.50) and close to rural areas (5.7% vs. 10.3 or 1.72, CI: 1.06-2.80) while Όχι significant changes were observed in urban areas (7.5% versus 7.6%, or 1.00, CI: 0.70 to 1.42).Ιncreases in asthma, eczema and rhinitis prevalence in both rural and urban areas. Conclusions: The prevalence of allergic diseases in Cyprus is still on the rise with recent increases appear more proΌχιunced among children living in rural areas possibly indicating recent environmental and lifestyle changes in these communities.
Keywords: Asthma; Wheezing; Allergies; Άσθμα; Συριγμός; Αλλεργίες; Αστικές Περιοχές